Evolution of Hot and Dense Stellar Interiors: The Role of the Weak Interaction Processes - Kosmas, T. S.; Tsoulos, I.; Kosmas, O.; Giannaka, P. G. (Frontiers in Astronomy and Space Sciences, 2022)
The evolution of the hot and dense interior of massive stars has aroused the intense interest of researchers the last more than three decades. In this article, the role of the semi-leptonic weak interaction processes of leptons (involving neutrinos) with nucleons and nuclei in the late stages of stellar evolution, as well as in the relevant terrestrial neutrino detection experiments, is reviewed. Such processes play crucial role for the massive stars’ evolution in the final stages of their life, and specifically in the core-collapse supernova leading to the supernova explosion phenomenon. We start by mainly focusing on the neutrino producing charged-lepton capture, like the electron-capture and the muon-capture on nuclei and, then, we discuss the neutrino absorbing reactions which are essential in the neutrino-driven explosive nucleo-synthesis. These processes are also significant in many ongoing and planned worldwide underground sensitive experiments aiming to detect astrophysical neutrinos which rely on the interactions of neutrinos with the bound nucleons inside atomic nuclei.